Kinetic Analysis of Amyloid Protofibril Dissociation and Volumetric Properties of the Transition State - Abdul Latif, Abdul Raziq; Kono, Ryohei; Tachibana, Hideki; Akasaka, Kazuyuki (Biophysical journal, 2007)
We present here the first detailed kinetic analysis of the dissociation reaction of amyloid protofibrils by utilizing pressure as an accelerator of the reaction. The experiment is carried out on an excessively diluted typical protofibril solution formed from an intrinsically denatured disulfide-deficient variant of hen lysozyme with Trp fluorescence as the reporter in the pressure range 3–400 MPa. From the analysis of the time-dependent fluorescence decay and the length distribution of the protofibrils measured on atomic force microscopy, we conclude that the protofibril grows or decays by attachment or detachment of a monomer at one end of the protofibril with a monomer dissociation rate independent of the length of the fibril. Furthermore, we find that the dissociation reaction is strongly dependent on pressure, characterized with a negative activation volume Δ V o‡ = −50.5 ± 1.60 ml mol −1 at 0.1 MPa and with a negative activation compressibility Δ κ ‡ = −0.013 ± 0.001 ml mol −1 bar −1 or −0.9 × 10 −6 ml g −1 bar −1. These results indicate that the protofibril is a highly compressible high-volume state, but that it becomes less compressible and less voluminous in the transition state, most probably due to partial hydration of the existing voids. The system eventually reaches the lowest-volume state with full hydration of the monomer in the dissociated state.